Mismatch repair protein expression in colorectal adenocarcinoma patients - Ngo, Quy Tran; Tran, Thi Nam Phuong; Nguyen, Tran Bao Song; Vo, Minh Hoang; Ngo, Cao Sach; Dang, Cong Thuan (Tạp chí Y Dược Huế, 2025)
Background: Colorectal cancer is the third most common cancer worldwide. Microsatellite instability (MSI) results from the functional deficiency of one of the mismatch repair (MMR) proteins, which can be identified using immunohistochemistry. Determining MMR status is crucial for clinicians in diagnosing, prognosticating, and making chemotherapy decisions for CRC patients. Objectives: (1) To assess the expression status of MMR proteins using immunohistochemistry. (2) To evaluate the association between MMR expression and certain clinicopathological features in colorectal adenocarcinoma. Materials and methods: A cross-sectional descriptive study was carried out on 81 colorectal cancer patients who were examined and treated at HueUniversity of Medicine and Pharmacy Hospital. The study was conducted from 04/2024 to 03/2025. Results: Deficient mismatch repair (dMMR) rate was 16%, proficient mismatch repair (pMMR) rate accounted for 84%. The tumors with dMMR status were significantly associated with right-sided location, tumor size larger than 5 cm, and moderate to poor differentiation (p < 0.05). There was no association between dMMR status and age, gender, histological subtype, T stage, lymph node metastasis, or disease stage. Conclusion: Testing for MMR status should be done for all patients with colorectal cancer, particularly those with right-sided tumors greater than 5 cm in size and high-grade histology.